Vicious and virtuous cycles of female labour force participation in post-socialist Eastern Europe - Sonja Avlijaš (London School of Economics and Political Science (LSE), European Institute, 2016)
Female labour force participation (hereinafter FLFP) trends across Eastern Europe, which were very high during communism, started to diverge substantially following its collapse. Women did not appear to benefit from the changing labour market conditions in those transition countries that pursued industrial upgrading as their strategy of economic development. On the other hand, in some small transition economies, most notably the Baltic countries, women benefited substantially from increased employment opportunities in the knowledge-intensive public and private sector services. This article seeks to explain the observed variation in FLFP rates across the region by synthesising insights from macroeconomic and comparative political economy literature. It identifies four key relationships between industrial upgrading, educational expansion and the expansion of knowledge-intensive services and examines how these factors interacted and translated into specific FLFP outcomes. The article suggests that industrial upgrading, driven by foreign direct investment, created a vicious cycle for FLFP. First of all, the upgrading led to a defeminisation of manufacturing because female labour-intensive sectors were not upgraded. Furthermore, the upgrading absorbed the budgetary resources that could have been used for educational reform and general skills formation. This lack of educational reform impeded the development of knowledge-intensive services, which would have been more conducive to the generation of female employment. The virtuous cycle of FLFP, on the other hand, occurred in those Eastern European countries that turned to reforming their ed-ucational sector towards general skills and expansion of tertiary education, with the aim of transforming themselves into knowledge economies. Such a transformation required an active social investment oriented state and an expansion of knowledge-intensive public and private sector employment. This development path created a positive causal loop for FLFP. I test these propositions quantitatively on a sample of 13 Eastern European countries.
Keywords: 330; female labour force participation; industrial upgrading; knowledge intensive economy; social investment; capitalist diversity; Eastern Europe